Global Stability Results in a SVIR Epidemic Model with Immunity Loss Rate Depending on the Vaccine-Age. (1st February 2015) - Peralta, Raúl; Vargas-De-León, Cruz; Miramontes, Pedro
Abstract : We formulate a susceptible-vaccinated-infected-recovered (SVIR) model by incorporating the vaccination of newborns, vaccine-age, and mortality induced by the disease into the SIR epidemic model. It is assumed that the period of immunity induced by vaccines varies depending on the vaccine-age. Using the direct Lyapunov method with Volterra-type Lyapunov function, we show the global asymptotic stability of the infection-free and endemic steady states.